LABORATORY EVALUATION OF CIPUNAGARA RIVER AGGREGATE AS A COMPONENT OF ASPHALT CONCRETE BINDER COURSE MIXTUR - Yandi, Chairal
LABORATORY EVALUATION OF CIPUNAGARA RIVER AGGREGATE AS A COMPONENT OF ASPHALT CONCRETE BINDER COURSE MIXTURE, Chairal Yandi, 2000, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. Aggregate deposits along the Cipunagara river in the Subang Regency are a potential source of material for the construction of the proposed Cikampek-Cirebon toll highway. The research described in this thesis was concerned with an evaluation of the engineering properties of Cipunagara aggregate and of asphalt concrete binder course made with the aggregate. Test were conducted on crushed coarse and fine aggregate and on the natural fine aggregate. For purpose of comparison a parallel investigation was conducted using aggregate from Banjaran. Petrography test were conducted on aggregate from both sources. The test data indicate that the Cipunagara aggregate satisfies specified and recommended strength, hardness and durability requirements'for aggregate used in binder course mix. However the water absorption of the Cipunagara natural fine aggregate is relatively high and exceeds the maximum permitted value of 3%. The Marshall procedure was used to design mixes containing crushed coarse and fine Banjaran aggregate (Mixture I), crushed coarse and fine Cipunagara aggregate (Mixture II) and crushed coarse and natural fine Cipunagara aggregate (Mixture III). At optimum bitumen content the three mixtures satisfied Bina Marga mix design criteria. Mixtures at optimum bitumen content were tested for durability, indirect tensile strength and resilient modulus and resistance to defoLnlation. The three mixtures had an Index of Retained Stability greater than 75%, the minimum value specified by Bina Marga. At 35°C and 45°C, Mixture I had the highest indirect tensile strength, followed by Mixtures II and III. At these two temperatures Mixture I had the highest resilient modulus while that of Mixture III was higher than that of Mixture II. All three mixes had similar resistance to permanent deformation at 30°C, 45°C and 60°C. The results of the investigation indicate that a satisfactory asphalt concrete binder course mix can be made with Cipunagara aggregate and that in general better performance is achieved if crushed fine aggregate is used